GABAergic polygenic risk for cocaine use disorder is negatively correlated with precuneus activity during cognitive control in African American individuals. (March 2021) - Yang, Bao-Zhu; Balodis, Iris M.; Kober, Hedy; Worhunsky, Patrick D.; Lacadie, Cheryl M.; Gelernter, Joel; Potenza, Marc N.
Highlights: GABA polygenic risk scores (PRSs) for cocaine use disorder (CUD) differ between cases and controls. GABA PRSs relate inversely with Stroop neural correlates in the left precuneus in CUD. Seed-based connectivity identified reduced precuneus-to-posterior-cingulate connectivity in CUD. Abstract: Impaired cognitive control has been implicated in cocaine use disorder (CUD). GABAergic treatments have been proposed for CUD. Here we examined relationships between GABAergic genes and neural correlates of cognitive control in CUD. We analyzed two independent African American cohorts: one of >3000 genomewide-genotyped subjects with substance dependence and another of 40 CUD and 22 healthy control (HC) subjects who were exome-array genotyped and completed an fMRI Stroop task. We used five association thresholds to select variants of GABAergic genes in the reference cohort, yielding five polygenic risk scores (i.e., CUD-GABA-PRSs) for the fMRI cohort. At p  < 0.005, the CUD-GABA-PRSs, which aggregated relative risks of CUD from 89 variants harboring in 16 genes, differed between CUD and HC individuals in the fMRI sample ( p  = 0.013). This CUD-GABA-PRS correlated inversely with Stroop-related activity in the left precuneus in CUD ( r  = −80.58, p FWE  < 0.05) but not HC participants. Post-hoc seed-based connectivity analysis of the left precuneus identified reduced functional connectivity to the posterior cingulate cortex (PCC) in CUD compared to HC subjects ( p  = 0.0062) and the degree of connectivity correlated with CUD-GABA-PRSs in CUD individuals ( r  = 0.287, p  = 0.036). Our findings suggest that the GABAergic genetic risk of CUD in African Americans relates to precuneus/PCC functional connectivity during cognitive control. Identification of these GABAergic processes may be relevant targets in CUD treatment. The novel identification of 16 GABAergic genes may be investigated further to inform treatment development efforts for this condition that currently has no medication with a formal indication for its treatment.